Case Report: Management of Cholestasis Associated With Congenital Syphilis - Ogawa, Kotaro; Kawase, Koya; Sugiura, Tokio; Yasui, Toshihiro; Yamagata, Seiya; Watanabe, Tamao; Kawabe, Yoshikazu (Frontiers in Pediatrics, 2020)
Cholestasis is a rare, but life-threatening, complication of congenital syphilis. However, standard management methods for this disease are not established. Here, we report a case of congenital syphilis presenting with progressively worsening cholestasis and we review the clinical features and management practices. In these cases, differentiation from other diseases presenting with cholestasis during the neonatal period, such as biliary atresia, is critical. In this regard, operative cholangiogram and histopathological analysis of the liver are required. Moreover, comprehensive genetic analysis can be useful. Although there is no specific treatment for cholestasis associated with congenital syphilis, appropriate nutritional management and supplementation with fat-soluble vitamins, especially vitamin K, should be provided. The severity of liver fibrosis may affect the prognosis of cholestasis associated with congenital syphilis. Therefore, attention should be paid to liver fibrosis in these patients.